Ergonomic Checkpoint in Agriculture, Postural Analysis, and Prevalence of Work Musculoskeletal Symptoms among Indonesian Farmers: Road to Safety and Health in Agriculture - Ari Widyanti (Institute of Research and Community Outreach - Petra Christian University, 2018)
Agriculture is one of the most crucial and hazardous sectors in both the developing and the developed countries. The agriculture area has a various problem related to safety and health, calling an urgent research to solve the problem. The purpose of this study is to apply ergonomics checkpoint in agriculture (developed by ILO) in Indonesian as well as to observe the prevalence of musculoskeletal symptoms among Indonesian farmers.251 Indonesian farmers participate voluntarily in this study. “Ergonomic checkpoint in agriculture” as a tool to reduce agriculture-related accident and increase productivity is assessed by student researcher. Prevalence of musculoskeletal symptoms (MSS) is assessed using Nordic body map that is filling out by participants. Rapid Upper Limb Assessment (RULA), Rapid Entire Body Assessment (REBA), and postural analysis using 3 dimension Static Prediction Program (3D SSPP) are applied to observe the risk activities of Indonesian farmers including the manual hoe for land clearing, grass cutting for land clearing, planting the rice, manual plow, giving fertilizer, harvesting, threshing, cleaning the rice from the straw, and sun-drying of rice. According to ergonomics checkpoints, material handling and storage are the worst in Indonesian agriculture, coupled with minimum safety information, toilet and washing facilities, and first aid. The high-risk activities are manual hoe for land clearing, manual plow, grass cutting for land clearing and threshing. The reported MSS mainly found in the shoulder and lower back.In conclusion, Indonesian agriculture is in a poor ergonomics condition and is associated with high musculoskeletal symptoms. The postural analysis also reveals a high risk of farmer activities.